Oxazol-Fused Phenalenones: Tuning Fluorescence and Singlet Oxygen Generation with Solvent and Substituent - Silva-Molina, C; Silva-Molina, C; Sandoval-Altamirano, C (John Wiley and Sons Ltd, 2025)
Typically, singlet oxygen is generated by photosensitization, with 1H-phenalen-1-one (PN) being an efficient photosensitizer that achieves nearly unity quantum yield across various solvents. However, the molecule lacks the ability to fluoresce, which could otherwise provide spatiotemporal information for potential theranostic applications. Moreover, its absorption spectrum should be red-shifted to move toward the visible range, ideally approaching the therapeutic window without compromising ability to generate singlet oxygen. We resolved to explore the option of fusing new aromatic rings to the tricyclic PN structure. A series of 9-substituted 7H-phenaleno[2,1-d]oxazol-7-one were synthesized and characterized. The results indicate that introduction of an oxazole ring does not significantly disturb the efficient photosensitization of the core 1H-phenalen-1-one, as evidenced by 9-methyl-7H-phenaleno[2,1-d]oxazol-7-one) which presented ΦΔ near unity across various solvents; albeit it lacked fluorescence. In contrast, aromatic derivatives exhibit a balanced behavior between fluorescence and photosensitization. In polar protic media, fluorescence is preferred, while in apolar media, photosensitization is favored. The substituent effect was analyzed with electron-donating groups favoring non-radiative processes, particularly in polar media. Electron-attracting/neutral groups exhibited a mixed behavior between fluorescence, intersystem crossing (ISC), and non-radiative processes. Theoretical calculations suggest that observed excitation profiles and photochemical behavior correlates with electron density remotion from PN core. © 2025 Wiley-VCH GmbH.